PENGENALAN GREEN ECONOMY DAN PEMANFAATAN TEKNOLOGI PADA UMKM CIRENG BONTOT IBU SALMINAH - Badriah (TRIDAYA: Jurnal Pengabdian kepada Masyarakat, 2025)
In the era of globalization, the green economy is becoming increasingly relevant for increasing welfare and social equality while reducing environmental risks. UMKM, such as Cireng Bontot Ibu Salminah, have an important role in the economy and have the potential to implement green economy principles. On May 17 2024, the Pamulang Serang University Student Team held a community service to provide education about the green economy and the use of technology UMKM. This activity uses interactive counseling and discussion methods with two main sessions: green economy and the use of technology in marketing. In the green economy session, participants were given knowledge about the importance of reducing waste and using environmentally friendly packaging such as paper boxes. The technology utilization session focused on education about the use of social media platforms for promotion, even though UMKM face obstacles such as technological limitations. Alternative solutions and strategies for utilizing existing devices are discussed to overcome these obstacles. The results of this activity show an increase in environmental awareness and product sales. The education provided also strengthens customer loyalty through the use of environmentally friendly packaging and effective digital marketing strategies. This experience has had a real impact on UMKM and is a valuable lesson for students. Keywords: Green Economy; UMKM; Technology; Environmentally Friendly Packaging; Digital Marketing; Community Service